Digital transformation and social responsibility: pragmatism or the search for balance - M. A. Izmailova (Модернизация, инновация, развитие)
Purpose: the article defines modern approaches to establishing a balance between digital transformation and the social responsibility of the state and business based on identifying trends and principles for introducing digital technologies into human life, taking into account the priority of social responsibility.Methods: the study is based on a systematic approach to the digital transformation of society. Within the framework of this approach, the use of the achievements of scientific and technological progress is considered: in public administration – for the purpose of breakthrough development of the country and the interconnected solution of socio-economic problems; in the business sphere – to improve the quality of economic activity and strengthen competitive benefits.Results: a review of the current state of the digitalizing society, the demand for digital services and satisfaction with the quality of their receipt, the readiness of Russian regions to provide electronic public services. The trends of digital transformation of public administration and the stages of evolution of digital maturity of the state are revealed. It is emphasized that the successful solution of the issues of the digital agenda by the state becomes a stimulating factor in the digital development of business structures. The analysis of digital trends in the business environment has shown their conjugacy with the digitalization of public administration in the presence of a number of differences. The key role of company management in promoting the ideology of digital transformation is noted. Since the use of digital technologies, along with positive effects, can pose a threat to human security, the preservation of his rights and freedom, it becomes necessary to use the concept of social responsibility in carrying out digital transformations of society. The principles of social responsibility in carrying out digital transformations are defined.Conclusions and Relevance: the processes of digital transformation have firmly entered into all spheres of society. Despite the technological nature, digital development should take place in the logic of a humanistic approach. It is based on the principles of morality, recognition of the inviolability of human rights, with the emphasis on the importance of social responsibility of all actors of digital transformation. At the same time, Russia should build its own model of digital transformation based on respect for dignity, freedom and human rights guaranteed by the Constitution.